2015
DOI: 10.1080/09540121.2015.1062464
|View full text |Cite
|
Sign up to set email alerts
|

HIV-infected men who have sex with men, before and after release from jail: the impact of age and race, results from a multi-site study

Abstract: The U.S. HIV/AIDS epidemic is concentrated among men who have sex with men (MSM). Black men are disproportionately affected by incarceration and Black MSM experience higher infection rates and worse HIV-related health outcomes compared to non-Black MSM. We compared HIV treatment outcomes for Black MSM to other HIV-infected men from one of the largest cohorts of HIV-infected jail detainees (N=1,270) transitioning to the community. Of the 574 HIV-infected men released, 113 (19.7%) self-identified as being MSM. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 48 publications
3
29
1
Order By: Relevance
“…These groups, particularly HIV-infected MSM and transgender women, remain largely hidden within correctional populations and few studies have estimated their prevalence. The multi-site Enhance Link Initiative enrolled over 1200 HIV-infected persons with a history of jail incarceration and among these, 20% identified as MSM or bisexual [44], which was consistent with the proportion observed in our study. These findings and our results suggest that HIV-infected MSM, bisexuals, and transgender women may represent a larger proportion of HIV-infected persons behind bars than previously recognized.…”
Section: Discussionsupporting
confidence: 87%
“…These groups, particularly HIV-infected MSM and transgender women, remain largely hidden within correctional populations and few studies have estimated their prevalence. The multi-site Enhance Link Initiative enrolled over 1200 HIV-infected persons with a history of jail incarceration and among these, 20% identified as MSM or bisexual [44], which was consistent with the proportion observed in our study. These findings and our results suggest that HIV-infected MSM, bisexuals, and transgender women may represent a larger proportion of HIV-infected persons behind bars than previously recognized.…”
Section: Discussionsupporting
confidence: 87%
“…Vagenas et al found that pre-incarceration, young African-American MSM had significantly less insurance and less access to HIV health care during incarceration. 142 Young African-American MSM were less likely to receive disease management and were less likely to be linked to HIV care post-incarceration. 142 …”
Section: Mental Health and Hiv Prevention Engagement And Carementioning
confidence: 98%
“…142 Young African-American MSM were less likely to receive disease management and were less likely to be linked to HIV care post-incarceration. 142 …”
Section: Mental Health and Hiv Prevention Engagement And Carementioning
confidence: 98%
“…The HIV epidemic disproportionately affects the incarcerated population in the US, with a 1.3% seroprevalence that is approximately three times that of the general population [1]. Furthermore, compared to people living with HIV (PLH) in the US general population, incarcerated PLH are often less likely to have achieved HIV care continuum milestones [2,3] -engaged in care, received and adhered to antiretroviral therapy (ART) and achieved virologic suppression -at the time of incarceration [4][5][6][7]. The disproportionate burden as well as the profound challenges in achieving the care continuum reflect how the incarcerated population represents one of the most socially and economically marginalized individuals in the US [8][9][10].…”
Section: Introductionmentioning
confidence: 99%